Merkmalloses versus pluralisches/distributives/intensives Partizip - Schenkel, Wolfgang (Zeitschrift für ägyptische Sprache und Altertumskunde, 2011)
Traditionally (Sethe/Gardiner), the difference between reduplicated (formerly ‘geminated’) and non-reduplicated participles is seen to lie in tense/ aspect. According to more recent interpretations, the choice of the reduplicated participle is determined by the aspect of plurality (Schenkel), distributivity (Allen) and/or intensification (Jansen-Winkeln). The observation that provided a point of departure (Schenkel), and which now forms the basis for a refutation (Depuydt), is the juxtaposition of phrases such as mr.y it(i)=f “beloved of his father” and mrr.w sn(·w.w)=f “beloved of his brothers”. The thesis presented here is that in the case of mr.y as opposed to mrr.w , for example, we are dealing not with a simple paradigmatic opposition of participles but rather that mr.y , which lexicographers have classified as a participle, is in fact a substantivized participle, i.e. is a substantive, whereas mrr.w , which pre-Polotsky, when used in relative constructions, was considered to be a participle, should, according to Polotsky, be understood as a Relative Form and not a participle. As a consequence, the juxtaposition of mr.y and mrr.w alone does not enable one to prove either the contextual (paradigmatic) relevance or irrelevance of the aspects of plurality, distributivity or intensification. Not affected is the co-textual relevance of plurality, distributivity or intensification since the choice of reduplicated Relative Forms obviously (also) depends on co-textual factors.